Evaluation of Legal and Policy Issues in Consumer Protection in Indonesian Fintech Transactions - Yuyut Prayuti (LEGAL BRIEF, 2024)
Indonesia's fintech industry has grown rapidly, with transactions reaching more than IDR 15 trillion by 2023, but this growth has also brought significant challenges such as fraud and data leaks that highlight weaknesses in consumer protection. Regulations such as OJK Regulation No. 77/POJK.01/2016 and Government Regulation No. 71 of 2019 have been implemented to balance innovation and consumer protection, but still require further evaluation for their adequacy. The study aims to assess the effectiveness of these regulations in identifying, preventing, and addressing fraud and privacy violations, as well as supporting the continued growth of the fintech industry. Using juridical-normative methodology with statutory, comparative, and conceptual approaches, this study seeks to map weaknesses in the existing legal framework and propose possible improvements. The results of this study are expected to provide practical recommendations to strengthen fintech regulation in Indonesia, support the growth of the digital economy while protecting consumer rights